NEW TECHNOLOGY FOR GROWING MICROORGANISMS OF THE BACILLUS SP, RHIZOBIUM SP, AZOTOBACTER SP. - Vokkosov, Zuhriddin; Abdulxoshim, Kadirov (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article studies a new technology for growing and multiplying Bacillus sp., Rhizobium sp., and Azotobacter sp. microorganisms on the surface of a nutrient medium. In the research process, peanut oil and grape pomace were used as natural substrates. The pH of the nutrient medium was maintained at 5.7-6.2, and the temperature was maintained at 35-37°C. Micro- and macroelements were added in a balanced manner. As a result of the experiment, a 2-8-fold increase in the growth of microorganisms was observed. This new technology allows for the efficient use of natural resources and can be used in the production of biofertilizers.